TECHNICAL INSPECTION AND STRENGTHENING OF A WIND POWER PLANT STRUCTURE - Rutkovska , І.; Fabryka , Ю. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
The article examines current issues related to the technical inspection and strengthening of buildings and structures in the context of modern requirements for reliability, durability, and safety. Methodological approaches to assessing the technical condition of facilities are presented, including visual inspection, instrumental measurements, non-destructive testing, and the use of digital monitoring technologies. The main factors contributing to the reduction of structural performance are analyzed, particularly material aging, environmental impact, dynamic and man-made loads, as well as construction technology violations. The article presents the results of a technical inspection of the foundation of a wind energy installation located within the Skybova zone of the Beskyd part of the Carpathians. The geological, climatic, and structural characteristics of the site and the structure are described. The aim of the research is to determine the current technical condition of the load-bearing elements, identify structural defects, and develop effective methods for strengthening the concrete foundation. The inspection was carried out in several stages using visual, instrumental, and laboratory testing methods. Local voids and zones of reduced concrete density were identified, which decrease the load-bearing capacity of the foundation. To eliminate these defects, a strengthening technology using SikaGrout®-3350 - a one-component, non-shrink, high-strength cementitious grout - was proposed. The article details the sequence of repair operations, material preparation and injection procedures, and quality control requirements. The proposed solution restores the monolithic integrity of the concrete foundation, improves its reliability, and extends its service life without dismantling the structure. The obtained results can be applied to similar renewable energy projects, especially in seismically active and geotechnically complex mountain regions of Ukraine.